1987
DOI: 10.1177/028418518702800106
|View full text |Cite
|
Sign up to set email alerts
|

Radiography and Ultrasonography in Paranasal Sinusitis

Abstract: In order to analyze whether ultrasonography with a reasonable degree of confidence can replace radiography in the diagnosis of sinusitis, 138 patients with clinical signs of sinusitis were examined with both methods. It was found that maxillary sinus fluid was recognized ultrasonographically with a confidence that increased with the amount of fluid, judged from radiographic examinations. In a sub-group of 45 cases, fluid confirmed by maxillary sinus puncture was detected by ultrasonography in 35/45 sinuses (78… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…In previous studies [5][6][7][8][9][10] comparing ultrasonography with radiography in the detection of maxillary sinusitis, the sensitivity of ultrasound ranged from 32% to 99% and the specificity ranged from 61% to 100%. The comparability of these studies, however, is limited because of extensive methodological variation.…”
Section: Commentmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies [5][6][7][8][9][10] comparing ultrasonography with radiography in the detection of maxillary sinusitis, the sensitivity of ultrasound ranged from 32% to 99% and the specificity ranged from 61% to 100%. The comparability of these studies, however, is limited because of extensive methodological variation.…”
Section: Commentmentioning
confidence: 99%
“…In addition, the exact criteria used for diagnosing sinusitis by ultrasonography and radiography were reported in only 2 of these studies. 8,9 Conventionally, only ultrasound findings indicative of the presence of fluid in the sinus (echo, Ͼ3.5-4.0 cm) have been interpreted as maxillary sinusitis. 8,9,14 In radiological imaging, however, considerable mucosal thickening even in the absence of an air-fluid level is generally regarded as evidence of sinusitis.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…Using A-US and Xray to evaluate antral mucosal thickening in chronic sinusitis, Druce et al (1988) found the total specificity to be 61% and the sensitivity 34% (15). In a study by Jensen and von Sydow (1987) the A-US findings of mucosal thickening without fluid correlated with Xray in only 19% and different degrees of mucosal thickening were poorly demonstrable (16).…”
Section: Introductionmentioning
confidence: 99%
“…The primary care setting often lacks facilities for a precise diagnosis, and general practitioners (GPs) have had to rely on their clinical judgement despite the uncertainty involved (1,4). Radiography is usually considered reliable for showing secretion in nasal cavities (5,6), while the opinions on the accuracy of the ultrasound vary (3,5,7). Ultrasonography has been promoted as an easy and readily accessible method in primary care and it is used increasingly.…”
mentioning
confidence: 99%